Preparation method of tunnel type sodium battery positive electrode material
By doping high-entropy anions into the positive electrode material of sodium ion battery, it is induced to form a tunnel structure, and the problem of difficult to take into account both electrochemical performance and stability in the prior art is solved, and the preparation of tunneled sodium electrode materials with high cyclic stability and high discharge capacity is achieved, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202510300577.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-14
AI Technical Summary
The layered oxide cathode materials of existing sodium ion batteries are difficult to balance the electrochemical performance and stability, and the preparation process is complex, which limits large-scale production.
By doping high entropy anions into the layered sodium electropositive electrode material, it is induced to form a tunnel structure, and then pressed into a cylinder with a tablet press and then subjected to high-temperature treatment and cooling grinding, the tunneled sodium electropositive electrode material prepared has a molecular formula of Na0.67MnOFaClbBrcBd.
The cycle stability of tunnel-type sodium electropositive electrode material and the improvement of half-cell discharge capacity are achieved, capacity attenuation is avoided, and the preparation process is simplified, cost is reduced, and it is suitable for large-scale production.
Smart Images

Figure CN119822387A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and specifically relates to a method for preparing a tunnel-type sodium battery positive electrode material. Background Art
[0002] Sodium-ion batteries are regarded as an ideal alternative to lithium-ion batteries due to their low cost and excellent safety performance. In recent years, with the growing global demand for battery energy storage systems, sodium-ion batteries can provide a more cost-effective alternative to existing lithium-based energy storage systems with their economy and safety, especially for large-scale energy storage applications that are sensitive to safety and cost. Sodium-ion battery cathode materials are mainly divided into three categories: layered metal oxides, polyanionic compounds, and Prussian blue compounds. Among them, layered sodium-based manganese oxide has low cost and relatively reversible sodium ion insertion / extraction characteristics, and is a sodium-ion battery cathode material with potential application prospects. However, the manganese redox reaction inevitably produces the Jahn-Teller effect, causing severe lattice distortion and leading to significant capacity decay. Compared with the limited two-dimensional sodium ion transmission path of the layered cathode, the tunnel-type sodium cathode can achieve isotropic sodium ion diffusion through its three-dimensional interconnected S-type channel network. This feature can greatly inhibit the Jahn-Teller effect, significantly reduce the activation energy of sodium ion migration, and effectively alleviate the concentration polarization phenomenon during high-rate charge and discharge. In addition, the intrinsic rigid framework of the tunnel structure can significantly inhibit the initiation and expansion of microcracks caused by volume deformation during the deep sodium extraction process. Therefore, the tunnel-type sodium cathode has irreplaceable advantages in the field of new energy, especially in scenarios such as fast charging and long life applications.
[0003] Patent CN118908304A discloses a single-crystal layered sodium positive electrode material which uses organic amines as structural templates and adopts a solvothermal method to initially form crystal nuclei, and then adopts a gradual sodium addition method for high-temperature solid-phase synthesis. The material has high energy density and cycle stability in terms of electrochemical performance, but its complex preparation process makes it extremely limited under large-scale demand.
[0004] Therefore, exploring a new method for preparing tunnel-type sodium cathode materials has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a tunnel-type sodium-based positive electrode material. The tunnel-type sodium-based positive electrode material prepared by the method has the characteristics of good cycle stability and high half-cell discharge capacity.
[0006] The method for preparing the tunnel-type sodium positive electrode material of the present invention comprises the following steps: (1) using sodium carbonate as a sodium source, manganese trioxide as a manganese source, and a mixture of sodium fluoride, sodium chloride, sodium bromide, and boron oxide as a doping source of high entropy anions, grinding the sodium source, manganese source, and the doping source of high entropy anions in an agate mortar for 25-35 minutes to mix them evenly, thereby preparing a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF a Cl b Br c B d , where 0.005≤a≤0.035, 0.005≤b≤0.035, 0.005≤c≤0.035, 0.005≤d≤0.035.
[0007] in: The molar ratio of sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride, sodium bromide and boron oxide in the mixture of step (1) is 0.67:1:a:b:c:d, wherein 0.005≤a≤0.035, 0.005≤b≤0.035, 0.005≤c≤0.035, and 0.005≤d≤0.035.
[0008] The pressure of the tablet press in step (2) is 400-500N.
[0009] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0010] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0011] The tunnel-type sodium cathode material prepared in step (2) needs to be stored in a dry environment at 60-80° C. to avoid contamination by water vapor.
[0012] Preferably, the molecular formula of the tunnel-type sodium cathode material prepared in step (2) is Na 0.67 MnOF a Cl b Br c B d , where a is 0.030, b is 0.005, c is 0.030, and d is 0.030.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The method for preparing the tunnel-type sodium positive electrode material of the present invention solves the technical problems of the inability to balance electrochemical performance and stability and the complex preparation process of the layered oxide positive electrode material of the sodium ion battery by doping high entropy anions into the layered sodium positive electrode material to induce it to become a tunnel-type sodium positive electrode material.
[0014] (2) The preparation method of the tunnel-type sodium cathode material described in the present invention, through which an irregular polyhedron consisting of a MnO4 quadrilateral pyramid and two or three groups of MnO6 octahedra is constructed. These octahedra establish large tunnels and smaller inactive channels. These tunnels can better withstand the lattice distortion caused by the reversible insertion / extraction of sodium ions, thereby avoiding capacity decay, which is impossible for layered sodium cathode materials.
[0015] (3) The tunnel-type sodium battery positive electrode material prepared by the preparation method of the present invention has a stable product structure. The half-cell formed by using it as the sodium battery positive electrode has a high discharge capacity and good cycle stability. In addition, its simple preparation process is low in cost and easy to achieve large-scale batch production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a SEM image of the tunnel-type sodium cathode material prepared in Example 1; Figure 2 The X-ray diffraction pattern of the tunnel-type sodium positive electrode material prepared in Example 1; Figure 3 The X-ray diffraction pattern of the layered sodium positive electrode material prepared in Comparative Example 1; Figure 4 The figure is a comparison chart of the cycle performance of the sodium battery positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-5. DETAILED DESCRIPTION
[0017] The present invention is further described below with reference to the embodiments.
[0018] Example 1 The method for preparing the tunnel-type sodium positive electrode material described in this embodiment 1 comprises the following steps: (1) Sodium carbonate is used as a sodium source, manganese trioxide is used as a manganese source, and a mixture of sodium fluoride, sodium chloride, sodium bromide and boron oxide is used as a doping source of high entropy anions. The sodium source, manganese source and the doping source of high entropy anions are ground in an agate mortar for 30 minutes and mixed evenly to prepare a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF aCl b Br c B d , where a is 0.030, b is 0.005, c is 0.030, and d is 0.030.
[0019] in: The molar ratio of sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride, sodium bromide and boron oxide in the mixture of step (1) is 0.67:1:a:b:c:d, wherein a is 0.030, b is 0.005, c is 0.030 and d is 0.030.
[0020] The pressure of the tablet press in step (2) is 450N.
[0021] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0022] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0023] The tunnel-type sodium cathode material prepared in step (2) needs to be stored in a dry environment at 70° C. to avoid contamination by water vapor.
[0024] The tunnel type sodium positive electrode material prepared in Example 1 was subjected to SEM testing, and its SEM image is shown in the attached figure. Figure 1 As shown; the X-ray diffraction test was carried out on it, and its X-ray diffraction pattern is as shown in the attached Figure 2 shown.
[0025] Example 2 The method for preparing the tunnel-type sodium positive electrode material described in this embodiment 2 comprises the following steps: (1) Sodium carbonate is used as a sodium source, manganese trioxide is used as a manganese source, and a mixture of sodium fluoride, sodium chloride, sodium bromide and boron oxide is used as a doping source of high entropy anions. The sodium source, manganese source and the doping source of high entropy anions are ground in an agate mortar for 25 minutes and mixed to obtain a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF a Cl b Br c B d , where a is 0.030, b is 0.020, c is 0.030, and d is 0.030.
[0026] in: The molar ratio of sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride, sodium bromide and boron oxide in the mixture of step (1) is 0.67:1:a:b:c:d, wherein a is 0.030, b is 0.020, c is 0.030 and d is 0.030.
[0027] The pressure of the tablet press in step (2) is 400N.
[0028] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0029] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0030] The tunnel-type sodium cathode material prepared in step (2) needs to be stored in a dry environment at 60° C. to avoid contamination by water vapor.
[0031] Example 3 The method for preparing the tunnel-type sodium positive electrode material described in this embodiment 3 comprises the following steps: (1) Sodium carbonate is used as a sodium source, manganese trioxide is used as a manganese source, and a mixture of sodium fluoride, sodium chloride, sodium bromide and boron oxide is used as a doping source of high entropy anions. The sodium source, manganese source and the doping source of high entropy anions are ground in an agate mortar for 35 minutes to be uniformly mixed to prepare a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF a Cl b Br c B d , where a is 0.005, b is 0.005, c is 0.005, and d is 0.005.
[0032] in: The molar ratio of sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride, sodium bromide and boron oxide in the mixture of step (1) is 0.67:1:a:b:c:d, wherein a is 0.005, b is 0.005, c is 0.005 and d is 0.005.
[0033] The pressure of the tablet press in step (2) is 500N.
[0034] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0035] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0036] The tunnel-type sodium cathode material prepared in step (2) needs to be stored in a dry environment at 80° C. to avoid contamination by water vapor.
[0037] Example 4 The method for preparing the tunnel-type sodium positive electrode material described in this embodiment 4 comprises the following steps: (1) Sodium carbonate is used as a sodium source, manganese trioxide is used as a manganese source, and a mixture of sodium fluoride, sodium chloride, sodium bromide and boron oxide is used as a doping source of high entropy anions. The sodium source, manganese source and the doping source of high entropy anions are ground in an agate mortar for 33 minutes and mixed to obtain a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF a Cl b Br c B d , where a is 0.035, b is 0.035, c is 0.035, and d is 0.035.
[0038] in: The molar ratio of sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride, sodium bromide and boron oxide in the mixture of step (1) is 0.67:1:a:b:c:d, wherein a is 0.035, b is 0.035, c is 0.035 and d is 0.035.
[0039] The pressure of the tablet press in step (2) is 480N.
[0040] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0041] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0042] The tunnel-type sodium cathode material prepared in step (2) needs to be stored in a dry environment at 75° C. to avoid contamination by water vapor.
[0043] Example 5 The method for preparing the tunnel-type sodium positive electrode material described in this embodiment 5 comprises the following steps: (1) Sodium carbonate is used as a sodium source, manganese trioxide is used as a manganese source, and a mixture of sodium fluoride, sodium chloride, sodium bromide and boron oxide is used as a doping source of high entropy anions. The sodium source, manganese source and the doping source of high entropy anions are ground in an agate mortar for 30 minutes and mixed evenly to prepare a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF a Cl b Br c B d , where a is 0.030, b is 0.030, c is 0.030, and d is 0.030.
[0044] in: The molar ratio of sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride, sodium bromide and boron oxide in the mixture of step (1) is 0.67:1:a:b:c:d, wherein a is 0.030, b is 0.030, c is 0.030 and d is 0.030.
[0045] The pressure of the tablet press in step (2) is 450N.
[0046] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0047] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0048] The tunnel-type sodium cathode material prepared in step (2) needs to be stored in a dry environment at 70° C. to avoid contamination by water vapor.
[0049] Comparative Example 1 The method for preparing the layered sodium positive electrode material described in this comparative example 1 comprises the following steps: (1) Using sodium carbonate as a sodium source and manganese trioxide as a manganese source, grinding the sodium source and the manganese source in an agate mortar for 30 minutes to mix them evenly, thereby preparing a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a layered sodium positive electrode material. The molecular formula of the layered sodium positive electrode material is Na 0.67 MnO2.
[0050] in: The molar ratio of sodium carbonate to manganese trioxide in the mixture of step (1) is 0.67:1.
[0051] The pressure of the tablet press in step (2) is 450N.
[0052] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0053] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0054] The layered sodium cathode material prepared in step (2) needs to be stored in a dry environment at 70° C. to avoid contamination by water vapor.
[0055] The layered sodium positive electrode material prepared in Comparative Example 1 was subjected to SEM testing, and its SEM image is shown in the attached figure. Figure 3 shown.
[0056] Comparative Example 2 The preparation method of the tunnel-type sodium positive electrode material described in this comparative example 2 consists of the following steps: (1) grinding sodium carbonate, manganese trioxide and sodium fluoride in an agate mortar for 30 minutes to mix uniformly to prepare a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF a , where a is 0.035.
[0057] in: The molar ratio of sodium carbonate, manganese trioxide and sodium fluoride in the mixture of step (1) is 0.67:1:0.035.
[0058] The pressure of the tablet press in step (2) is 450N.
[0059] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0060] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0061] The tunnel-type sodium cathode material prepared in step (2) needs to be stored in a dry environment at 70° C. to avoid contamination by water vapor.
[0062] Comparative Example 3 The preparation method of the tunnel-type sodium positive electrode material described in this comparative example 3 consists of the following steps: (1) grinding sodium carbonate, manganese trioxide, sodium fluoride, sodium bromide and boron oxide in an agate mortar for 30 minutes to mix uniformly to prepare a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF a Br c B d , where a is 0.030, c is 0.030, and d is 0.030.
[0063] in: The molar ratio of sodium carbonate, manganese trioxide, sodium fluoride, sodium bromide and boron oxide in the mixture of step (1) is 0.67:1:0.030:0.030:0.030.
[0064] The pressure of the tablet press in step (2) is 450N.
[0065] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0066] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0067] The tunnel-type sodium cathode material prepared in step (2) needs to be stored in a dry environment at 70° C. to avoid contamination by water vapor.
[0068] Comparative Example 4 The preparation method of the tunnel-type sodium positive electrode material described in this comparative example 4 is composed of the following steps: (1) grinding sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride and boron oxide in an agate mortar for 30 minutes to mix uniformly to prepare a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF a Cl b B d , where a is 0.030, b is 0.030, and d is 0.030.
[0069] in: The molar ratio of sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride and boron oxide in the mixture of step (1) is 0.67:1:0.030:0.030:0.030.
[0070] The pressure of the tablet press in step (2) is 450N.
[0071] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0072] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0073] The tunnel-type sodium cathode material prepared in step (2) needs to be stored in a dry environment at 70° C. to avoid contamination by water vapor.
[0074] Comparative Example 5 The preparation method of the tunnel-type sodium positive electrode material described in this comparative example 5 is composed of the following steps: (1) grinding sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride and sodium bromide in an agate mortar for 30 minutes to mix uniformly to prepare a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF a Cl b Br c , where a is 0.030, b is 0.030, and c is 0.030.
[0075] in: The molar ratio of sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride and sodium bromide in the mixture of step (1) is 0.67:1:0.030:0.030:0.030.
[0076] The pressure of the tablet press in step (2) is 450N.
[0077] The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
[0078] The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
[0079] The tunnel-type sodium cathode material prepared in step (2) needs to be stored in a dry environment at 70° C. to avoid contamination by water vapor.
[0080] By analyzing the X-ray diffraction patterns of Example 1 and Comparative Example 1, Figure 2 The diffraction peaks show a typical tunnel structure. For example, the reflection (101) at about 2θ = 10°1 is a typical feature of this structure. However, the X-ray diffraction peaks show that there are still a small amount of P2 layered peaks, but the signal intensity is extremely low. Figure 1 is a SEM image of Example 1, showing that its microstructure is tunnel-type, which is consistent with its X-ray diffraction result. Figure 3 This is the X-ray diffraction pattern of comparative example 1, which corresponds to the diffraction peak of the P2 phase, and the reference component is the layered structure of Na0.67MnO2. It is not difficult to see that the doping of high entropy anions has a huge impact on the structural properties of Na0.67MnO2, successfully inducing the layered structure to a tunnel-type structure, but in this process, the doping of fluorine ions will affect the size of the tunnel and the layer / tunnel ratio. The synthesis with a higher fluorine dosage will cause the layered structure to be transformed into a tunnel-like structure in large quantities due to the preferred orientation of fluorine ions.
[0081] The positive electrode materials obtained in Examples 1-5 and Comparative Examples 1-5 were respectively dispersed uniformly with Super P (super P conductive carbon black) and PVDF (polyvinylidene fluoride) in a solvent NMP (N-methylpyrrolidone) at a mass ratio of 8:1:1, and then the mixed slurry was coated on a base aluminum foil, dried, and cut into circular sheets; sodium sheets were used as electrodes, and sodium perchlorate was used as the electrolyte. The button cells were assembled for electrochemical performance testing. The test voltage range was 2.2V-4.3V, and the discharge specific capacity at a current density of 1C was recorded as a function of the number of cycles (wherein a current of 0.1C was applied in the first two cycles to activate the electrode), as shown in FIG. Figure 4 shown.
[0082] from Figure 4It can be concluded that: in Example 1, the first discharge specific capacity at 1C current is 157.43 mAh / g, and after 100 cycles, the discharge specific capacity of 1C is 126.57 mAh / g; in Example 2, the first discharge specific capacity at 1C current is 141.25 mAh / g, and after 100 cycles, the discharge specific capacity of 1C is 96.70 mAh / g; in Example 3, the first discharge specific capacity at 1C current is 112.58 mAh / g, and after 100 cycles, the discharge specific capacity of 1C is 97.22 mAh / g; in Example 4, the first discharge specific capacity at 1C current is 154.48 mAh / g, and after 100 cycles, the discharge specific capacity of 1C is 102.34 mAh / g; in Example 5, the first discharge specific capacity at 1C current is 153.42 mAh / g, and after 100 cycles, the discharge specific capacity of 1C is 120.11 mAh / g. In comparative example 1, the first discharge specific capacity at 1C current is 88.49 mAh / g, and after 100 cycles, the discharge specific capacity of 1C is 75.91 mAh / g; in comparative example 2, the first discharge specific capacity at 1C current is 109.02 mAh / g, and after 100 cycles, the discharge specific capacity of 1C is 92.23 mAh / g; in comparative example 3, the first discharge specific capacity at 1C current is 112.45 mAh / g, and after 100 cycles, the discharge specific capacity of 1C is 75.28 mAh / g; in comparative example 4, the first discharge specific capacity at 1C current is 82.75 mAh / g, and after 100 cycles, the discharge specific capacity of 1C is 76.93 mAh / g; in comparative example 5, the first discharge specific capacity at 1C current is 135.95 mAh / g, and after 100 cycles, the discharge specific capacity of 1C is 82.44 mAh / g. By comparing the data of each embodiment and each comparative example, it is not difficult to see that the discharge specific capacity scatter plot of the comparative example presents an undulating curve, while the scatter plot of the embodiment is relatively stable, which is sufficient to illustrate that the stability of the embodiment is better than that of the comparative example, demonstrating the improvement of the stability of the sodium ion battery by the tunnel shape.
[0083] By comparison, it is not difficult to see that the amount of doping with different anions has an impact on the capacity and cycle stability of the battery, but the embodiments involved are better than the layered sodium positive electrode material (Comparative Example 1). Through screening, whether it is the reversible charge and discharge capacity or the cycle stability performance, Example 1 is currently a relatively excellent high-entropy anion-doped tunnel-type sodium positive electrode material.
Claims
1. A method for preparing a tunnel-type sodium cathode material, characterized in that: It consists of the following steps: (1) using sodium carbonate as a sodium source, manganese trioxide as a manganese source, and a mixture of sodium fluoride, sodium chloride, sodium bromide, and boron oxide as a doping source of high entropy anions, grinding the sodium source, manganese source, and the doping source of high entropy anions in an agate mortar for 25-35 minutes to mix them evenly, thereby preparing a mixture; (2) The mixture prepared in step (1) is placed in a tablet press and pressed into a cylindrical shape, and then subjected to high temperature treatment, and finally ground after cooling to prepare a tunnel-type sodium positive electrode material. The molecular formula of the tunnel-type sodium positive electrode material is Na 0.67 MnOF a Cl b Br c B d , where 0.005≤a≤0.035, 0.005≤b≤0.035, 0.005≤c≤0.035, 0.005≤d≤0.
035.
2. The method for preparing a tunnel-type sodium positive electrode material according to claim 1, characterized in that: The molar ratio of sodium carbonate, manganese trioxide, sodium fluoride, sodium chloride, sodium bromide and boron oxide in the mixture of step (1) is 0.67:1: a: b: c: d, wherein 0.005≤a≤0.035, 0.005≤b≤0.035, 0.005≤c≤0.035, and 0.005≤d≤0.
035.
3. The method for preparing a tunnel-type sodium positive electrode material according to claim 1, characterized in that: The pressure of the tablet press in step (2) is 400-500N.
4. The method for preparing a tunnel-type sodium positive electrode material according to claim 1, characterized in that: The high temperature treatment in step (2) is to heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 12 hours.
5. The method for preparing a tunnel-type sodium positive electrode material according to claim 1, characterized in that: The grinding after cooling in step (2) is to cool to 150°C at a rate of 5°C / min, and then grind through a 400-mesh sieve.
6. The method for preparing a tunnel-type sodium positive electrode material according to claim 1, characterized in that: The molecular formula of the tunnel-type sodium cathode material prepared in step (2) is Na 0.67 MnOF a Cl b Br c B d , where a is 0.030, b is 0.005, c is 0.030, and d is 0.030.
Citation Information
Patent Citations
Fluorine ion doped manganese-based layered oxide positive electrode material with air stability and preparation method and application thereof
CN115188959A
Sodium-ion battery positive electrode material and preparation method thereof, positive electrode plate and sodium-ion battery
CN115440975A
Layered oxide material and preparation method and application thereof
CN115448321A
Method for rapidly synthesizing P2 '-Na < 0.67 > MnO2 positive electrode material and application of P2'-Na < 0.67 > MnO2 positive electrode material
CN116177606A
Positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
CN118248859A